PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MENGGUNAKAN METODE SILABA BERBANTUAN MEDIA SMART BOX PADA KELAS I SDN 06 PASAR AMBACANG - Kiki Firda Asmi; Ade Irma Suryani; Sisri Wahyuni; Yoga Suhendra; Yulmiati (STKIP Subang, 2026)
This research is motivated by the low initial reading skills of students in grade I of SDN 06 Pasar Ambacang. The study aims to describe the improvement of reading skills by using Smart Box media to improve reading skills in grade 1 students of SDN 06 Pasar Ambacang. This type of research is a Classroom Action Research (CAR) which consists of four stages, namely: planning, implementation, observation, and reflection. This research was conducted in two cycles. This research uses qualitative and quantitative approaches. The subjects of this study were grade 1 students of SDN 06 Pasar Ambacang with a total of 28 students. Data collection techniques consisted of observation, documentation, initial reading tests. The research instrument consisted of observation sheets, and documentation. The results of the study showed an increase in the initial reading skills of grade I students. The increase can be seen from the planning of the teaching module in cycle I was 72.77%, and the cycle II meeting was 85.18%. observation of the educator aspect in cycle I was 71.59%, and cycle II was 87.5%. observation of student aspects of cycle I is 72.82%, cycle II is 89.77%. the percentage of students' initial reading skills in cycle I meeting I is 60.67%, cycle I meeting II is 76%, cycle II meeting I is 84%. in cycle I meeting I the value of children in class I still get a K (less), then in cycle I meeting II already got a C (enough), still not maximum then the researcher maximized in cycle II meeting I the children already got a B. So the conclusion of the Silaba method assisted by Smart Box media can improve the reading skills of class I elementary school students.